Cover Image. Issue 12 (22nd July 2020) - Rashid, Barnaly; Calhoun, Vince
Abstract : COVER ILLUSTRATION A predictome refers to the use of multivariate brain network features from one or more neuroimaging modalities to help solve the puzzle of brain disorders. To build a predictome, one incorporates multiple brain network‐based features (either from the same modality or multiple modalities) into a predictive model to jointly estimate features that are unique to a disorder and are useful for individualized predictions.